1997
DOI: 10.1037/0735-7044.111.6.1245
|View full text |Cite
|
Sign up to set email alerts
|

Goal recognition and hippocampal formation in the homing pigeon (Columba livia).

Abstract: Stimulus control of food-site recognition and role of the hippocampal formation (HF) were investigated. Control and HF-lesioned pigeons were trained to find food located in a colored bowl, near a landmark beacon, in a constant room location. During later test trials, the sources of information were individually removed and/or disassociated. For all test trial types, HF-lesioned pigeons consistently chose bowls associated with one of the training stimuli. Controls were more sensitive to the changes introduced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
25
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
10
25
1
Order By: Relevance
“…If true, then neurons of this type could be described as 'context setting' cells. Consistent with the possible existence of context-setting neurons is the finding that, under some experimental conditions, HF lesions in homing pigeons can result in behavior suggestive of a loss of sensitivity to contextual stimuli [Strasser and Bingman, 1997].…”
Section: Spatial Response Properties Of Hf Neurons: a Preliminary Surveysupporting
confidence: 50%
“…If true, then neurons of this type could be described as 'context setting' cells. Consistent with the possible existence of context-setting neurons is the finding that, under some experimental conditions, HF lesions in homing pigeons can result in behavior suggestive of a loss of sensitivity to contextual stimuli [Strasser and Bingman, 1997].…”
Section: Spatial Response Properties Of Hf Neurons: a Preliminary Surveysupporting
confidence: 50%
“…Strasser and Bingman [1996] have found that homing pigeons, despite having a larger hippocampus than other non-homing pigeon breeds [Rehkaemper et al, 1988;Sherry et al, 1992], are not predisposed to use distal spatial cues over a combination of local landmarks and feature cues for recognition of a food site in the lab [Strasser and Bingman, 1996]. This result occurs despite the fact that hippocampal damage results in deficits in homing behaviors [Bingman et al, 1990;Bingman, 1992] and in spatial relations tasks [Strasser and Bingman, 1997], but not in non-spatial paired associations [Bingman et al, 1998]. Other studies have identified avian species with relatively small hippocampi that retrieve stored food caches without difficulty [Balda et al, 1998], and species with relatively large hippocampi that do not cache food [Volman et al, 1997].…”
Section: Discussionmentioning
confidence: 56%
“…After ablation of the piriform cortex both the learning [9] and the operation [17] of the navigational map were disrupted. Lesions of the hippocampal formation have suggested that this region is involved in spatial learning based on visual landmarks [2,25]. Furthermore, specific aspects of spatial information processing were separated.…”
Section: Introductionmentioning
confidence: 99%